Edukasi Terapi Komplementer dengan Rebusan Daun Salam pada Kestabilan Kadar Kolesterol Di Desa Krangganharjo Kec. Toroh - Sutiyono; Wahyu Riniasih; Suryani (LPPM AN Nuur, 2024)
Background: Elderly people often have high cholesterol. Hypercholesterolemia or often called high cholesterol is a medical disorder when blood cholesterol levels are higher than normal. Bay leaves (Syzgium Polyanthum) are among the plants recommended for consumption by hypercholesterolemia sufferers. Objective: To provide education about the benefits of bay leaves for hypercholesterolemia sufferers. Service Method: providing education and problem solving regarding hypercholesterolemia sufferersResults: Implementation of Health education was achieved 100% with the community understanding the use of bay leaves on cholesterol levels. There is a public willingness to implement the use of bay leaves for cholesterol levels